(3JYdjbI Ydi QjGV GdeSGFds - (3GdgQhj, GdGUagGfj, GdMGFQj, eMeO Jbj Hf MSjf Hf Ydj, J (B1299 (3g`s ((3MGLj cGXe GdCUagGfjs)
(3ChdgG (B:s
.. (3HYO GdGJeGe jYfj Cf GdMOK GdCUZQ GdhGbY HYO GJeGe GdZSd dG jfbV efg GdMcejf GdePchQjf EdG KGfjgeG ajLH GdhVhA M hdG jfbV ChdgeG ELeGYG Ch de jaJj GMO HhLhH GdZSd (B...s
(3BNQgG (B:s
.. (3hdG jNai Cf Shb GdNHQ hJUOjQg HGf QShd Gddg Udi Gddg Ydjg hSde GZJSd HUGY jCJj Yf Med Pjdg Ydi GdJbjI hcCfg ddETGQI Edi gPG GdCeQ HGdJCed (B. (3bO Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\ 179s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis